Targeted delivery of galunisertib using machine perfusion reduces fibrogenesis in an integrated ex vivo renal transplant and fibrogenesis model - van Leeuwen, LL; Ruigrok, MJR; Kessler, BM; Leuvenink, HGD; Olinga, P (Wiley, 2023)
Background and Purpose: Fibrosis in kidney allografts is a major post-transplant complication that contributes to graft failure. Lately, multiple potent inhibitors of fibrosis-related pathways have been developed such as galunisertib, an inhibitor of the transforming growth factor-beta (TGF-β/TGFβ1) signalling pathway. This drug, however, poses risks for adverse effects when administered systemically. Therefore, we devised a new repurposing strategy in which galunisertib is administered ex vivo. We combined machine perfusion and tissue slices to explore the antifibrotic effects of galunisertib in renal grafts.